Electrical property analytical prediction on archimedes chiral carbon nanoscrolls - Hassanzadazar, Mina (Springer New York LLC, 2016)
Carbon nanoscrolls (CNS) with flexible exterior areas and interesting electrical and mechanical properties have gained interest in recent years, both experimentally and theoretically. These structures have been employed as ion channels, tunable water channels, molecular sensors, and gene and drug distribution systems. In this study, electrical behaviour of all types of CNS containing armchair, zigzag, and chiral CNSs band structure is investigated. In armchair CNSs, the small band gap among valence and the conduction band as a pseudo-gap are reported, which reveals a semimetallic property for some of these CNSs. This small band gap, as a result of layer interaction, has been confirmed. Also, in many other types of armchair CNSs at the Fermi level, related levels cross each other, illustrating metallic characteristics. On the other hand, our numerical results show small band gaps for zigzag types of CNSs, which means that they are semiconductors. However, it cannot be considered as a general occurrence because only in rare circumstances is a very small band gap observed that gives rise to semimetallic CNSs. In addition, the electrical properties of chiral CNSs are explored. Small band gaps between the associated valence and the conduction band reveals that chiral CNSs mainly exhibit semiconducting behaviour. Finally, all the numerical results are tabulated in the form of a CNS periodic table and a symmetric arrangement with respect to the armchair nanoscrolls and as a table diagonal data for the chiral CNSs is noticed. In addition, this investigation highlights the variations of the energy structure of chiral CNSs with respect to their length. Presented results offer significant potential for chiral CNSs as an alternative to silicon-based sensors in nanotechnology. Therefore, the band gap variations in the presence of attached materials as a sensor platform need to be explored.